Marijuana Use Episodes and Partner Intimacy Experiences: A Daily Report Study - Testa, Maria (Cannabis, 2019)
Although marijuana use has been linked to negative consequences for intimate relationships, an emerging literature suggests that under some circumstances it may have positive consequences. Couples who use substances together report better relationship functioning over time and may experience positive short-term outcomes. Using a sample of 183 heterosexual, frequent marijuana-using couples from the community, reporting over 30 consecutive days, we examined whether marijuana use episodes were associated temporally with reports of couple intimacy experiences within the next two hours. We used multilevel modeling, within an Actor Partner Interdependence Model (APIM) framework, modeling male and female outcomes simultaneously. Consistent with hypotheses, simultaneous marijuana use (male and female partners reported use at the same hour) increased the likelihood of an intimate experience for both men and women. However, we also found positive effects for Actor and Partner solo marijuana use on male and female reports of intimacy events. When analyses were limited to marijuana use episodes in which the respondent reported on presence of partner, we found that positive effects on intimate experiences were limited to marijuana use episodes in which partner was present; use without partner did not influence likelihood of intimacy. The robust positive effects of using marijuana with one’s partner on intimacy events may serve to reinforce continued couple use and explain the positive effects of concordant substance use on relationship functioning over time.